VEGF‐B‐induced vascular growth leads to metabolic reprogramming and ischemia resistance in the heart. Issue 3 (21st January 2014) - Kivelä, Riikka; Bry, Maija; Robciuc, Marius R; Räsänen, Markus; Taavitsainen, Miia; Silvola, Johanna MU; Saraste, Antti; Hulmi, Juha J; Anisimov, Andrey; Mäyränpää, Mikko I; Lindeman, Jan H; Eklund, Lauri; et al.
Synopsis: Transgenic expression of VEGF‐B in the rat heart leads to expansion of the coronary arterial tree and an increase in functional coronary reserve, accompanied by a shift in myocardial metabolism from fatty acid to glucose utilization. VEGF‐B‐induced coronary artery growth protects the heart from ischemic damage Cardiac hypertrophy in VEGF‐B transgenic rats is physiological even in old age AAV‐VEGF‐B gene transfer to adult rats phenocopies the VEGF‐B transgenic rat heart Glucose uptake is increased and expression of fatty acid oxidation genes decreased in the VEGF‐B transgenic hearts VEGF‐B increases VEGF signaling via VEGFR‐2 Abstract: Angiogenic growth factors have recently been linked to tissue metabolism. We have used genetic gain‐ and loss‐of function models to elucidate the effects and mechanisms of action of vascular endothelial growth factor‐B (VEGF‐B) in the heart. A cardiomyocyte‐specific VEGF‐B transgene induced an expanded coronary arterial tree and reprogramming of cardiomyocyte metabolism. This was associated with protection against myocardial infarction and preservation of mitochondrial complex I function upon ischemia‐reperfusion. VEGF‐B increased VEGF signals via VEGF receptor‐2 to activate Erk1/2, which resulted in vascular growth. Akt and mTORC1 pathways were upregulated and AMPK downregulated, readjusting cardiomyocyte metabolic pathways to favor glucose oxidation and macromolecular biosynthesis. However, contrasting with a previous theory, there was no difference in fatty acid uptake by the heart between the VEGF‐B transgenic, gene‐targeted or wildtype rats. Importantly, we also show that VEGF‐B expression is reduced in human heart disease. Our data indicate that VEGF‐B could be used to increase the coronary vasculature and to reprogram myocardial metabolism to improve cardiac function in ischemic heart disease. Abstract : Transgenic expression of VEGF‐B in the rat heart leads to expansion of the coronary arterial tree and an increase in functional coronary reserve, accompanied by a shift in myocardial metabolism from fatty acid to glucose utilization.